(untitled) (Research, Society and Development, 2023)
Bearing in mind the high rates of car accidents that occur in the Northeast region, especially taking into account the incidence of hospitalizations due to Spinal Cord Injuries, it is therefore important to highlight the importance of this study, given that traffic accidents are one of the main causes of mortality. Thus, the objective of the research was to evaluate the incidence of cases of Spinal Cord Injuries caused by traffic accidents in the Northeast region. The method used for the study was a cross-sectional analysis. Data collection took place between January and February 2023, using the SUS Hospital Information System (SIH/SUS) and the Unified Health System Database (DATASUS). The results obtained indicate that the region that least notified cases of SCI was the Midwest region, with a total result of 514 confirmed cases in the last 3 years. These data point to the need to intensify and delimit these findings, since it is necessary to know the main factors responsible for these results and to delimit the states that have more evidence and notifications of traffic accidents with spinal cord injuries. In this outcome, the research was delimited, using the states of the northeast region to evaluate the notifications.